THE RELATIONSHIP OF PARENTING PATTERNS WITH THE EMOTIONAL DEVELOPMENT OF SCHOOL CHILDREN - Lola Azalia, Videla; Yunika Kristina Gea, Nurti; Nuryanti, Lisna (Journal of Vocational Nursing, 2024)
Introduction: Children are basically equipped with an emotional nature and must learn to regulate their emotions. Strong emotions can have an impact on a child's physical activity and can disrupt the balance of the child's body. Emotional development in children is influenced by parents' parenting patterns which include children's guidance in managing their internal and external lives. Parenting patterns that are less than optimal can cause anxiety and stress for both children and parents. Methods: This study investigates the relationship between parenting styles and emotional development in school-aged children (10-12 years). Using a descriptive-analytical approach with a cross-sectional design. Results: This study found a significant relationship between parental parenting style and children's emotional development. Specifically, 56.2% of children showed good emotional development, while 43.8% showed sufficient emotional development. Conclusions: These findings support the conclusion that parental parenting styles are related to the emotional development of school-aged children.